Light-Induced Inverse Electron Demand Diels-Alder Reaction as an Approach for Grafting Macromolecules to Glass Surfaces - Ozbek, Nagihan; Kahveci, Elif L. Sahkulubey; Kahveci, Muhammet Ubeydullah (AMER CHEMICAL SOC, 2021)
This study aims to develop a grafting technique for glass surfaces by light-induced inverse electron demand Diels-Alder (photo-IEDDA) reaction. The approach depends on the in situ formation of tetrazine molecule in the reaction medium and a subsequent IEDDA reaction of tetrazine moieties with trans-cyclooctene groups. First, light-induced formation of a tetrazine derivative from a precursor, 6-(6-(pyridin-2-yl)-1,4-dihydro-1,2,4,5-tetrazin-3-yl)pyridin-3-amine (PPA-dHTz), in the presence of a photosensitizer under visible light irradiation was evaluated by nuclear magnetic resonance (NMR) spectroscopy. For grafting glass surfaces, dihydrotetrazine (dHTz) end-functionalized poly(N-isopropylacrylamide) (PNIPAAm-dHTz) and poly((DL)-lactide) (PLA-dHTz) were prepared by reversible addition-fragmentation chain-transfer (RAFT) polymerization and ring-opening polymerization (ROP), respectively, and postpolymerization functionalization with a dihydrotetrazine molecule (PPA-dHTz). However, glass surfaces were decorated with trans-cyclooctenol (TCO) groups by functionalization with 3-aminopropyltriethoxysilane, succinic anhydride, and TCO successively. Then, photo-IEDDA was performed between the dHTz end-functionalized polymers and TCO-decorated glass surface in the presence of methylene blue and under visible light irradiation. To extend the applicability of the approach, grafting TCO-functionalized protein, namely, Concanavalin A-TCO, to dHTz-modified glass surface was achieved as well. In this case, glass surfaces were functionalized with PPA-dHTz. The successful polymer and protein grafting to glass surfaces were shown with X-ray photoelectron spectroscopy, contact angle measurement, scanning electron microscopy, atomic force microscopy, and Fourier transform infrared (FT-IR) spectroscopy.
Keywords: tetrazine; light-induced click; IEDDA; photooxidation; surface grafting glass surface; polymer; protein; CLICK CHEMISTRY; TRANS-CYCLOOCTENE; THIOL-ENE; BIOORTHOGONAL CHEMISTRY; TETRAZINE LIGATION; IMMOBILIZATION; CYCLOADDITION; ACTIVATION; FUNCTIONALIZATION; Materials Science; Polymer Science